HOTEL DESTINATION IMAGE AND HALAL - FRIENDLY SERVICE AND STAFF ON REVISIT INTENTION:A SYSTEMATIC LITERATURE REVIEW - Hendri, Naldi; Wardi, Yunia; Masdupi, Erni; Abror, Abror; Dwita, Vidyarini (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study aims to systematically identify, review, and assess the literature on the image of destination hotels and halal staff services in order to increase intention to return to hotels in Indonesia and provide an agenda for future research. The current study assesses existing revisit intentions on the topic, reveals limitations and gaps in the current literature, and suggests potential studies to further advance knowledge in this area. This research uses Systematic Literature Review. This study uses the keywords destination hotel image, halal staff service and intention to return. The research found 236 articles in the search using Science Direct and the help of other applications such as Mendeley, VOSViewer which were then filtered into 33 selected articles to be analyzed descriptively. Content analysis, assisted by Microsoft Excel, is used for review and analysis purposes. The findings show that affective destination image is positively related to intention to revisit and recommend , as well as to construct a series of product/service offering scenarios and then test the product/service offering scenario that best meets visitor expectations and also increases visitor satisfaction levels and their intention to return. Keywords: hotel destination i mage ; halal-friendly services and staff; re visit intention ; systematic literature review